The controversy on HPV vaccination in Japan: Criticism of the ethical validity of the arguments for the suspension of the proactive recommendation. Issue 2 (February 2020) - Okita, Taketoshi; Enzo, Aya; Kadooka, Yasuhiro; Tanaka, Masashi; Asai, Atsushi
Highlights: Japan suspending the official recommendation of the HPV vaccine for over 6 years. The arguments for the suspension not satisfying the requirements of public health ethics. The recommendation must either be reinstated or the HPV vaccine policy altered. Abstract: The Human Papillomavirus (HPV) vaccine was integrated into Japan's national immunization program (NIP) in April 2013. However, numerous instances of serious adverse reactions were widely reported in the media, resulting in the Ministry of Health, Labor, and Welfare (MHLW) suspending the official recommendation of the HPV vaccine on June 14, 2013. Investigating the reported incidents, the Vaccine Adverse Reactions Review Committee (VARRC)—an MHLW advisory committee—found no high-quality evidence supporting a causal relationship between the reported events and the HPV vaccination. However, rather than lifting the suspension, they have opted to maintain a "pseudo informed consent" confirming the perceptions of Japanese citizens regarding the vaccine. Accordingly, there appears to be a fundamental difference in the approach to vaccine policymaking between Japan (MHLW/VARRC) and other countries and the World Health Organization, which base policy decisions on the effectiveness and safety of the vaccine. Consequently, the arguments for the suspension of the HPV vaccine recommendation are not ethically appropriate. Relevant bodies must make a clear decision regarding the HPV vaccine and its status in the NIP: the proactive recommendation must either be reinstated or the HPV vaccine legal framework altered to rely entirely on voluntary individual decisions.